Acid-base cooperative catalysis over mesoporous nitrogen-rich carbon - Goyal, Reena; Sarkar, Bipul; Lucas, Nishita; Bordoloi, Ankur (ChemCatChem, 2014)
WOx nanoclusters (2-3 nm) embedded on a mesoporous nitrogen-rich carbon material were synthesized by using novel methodology. This material was very effectively capitalized as a new carbon-based acid-base cooperative catalyst for sequential acetal hydrolysis and Knoevenagel condensation reactions. The protocol was also explored for the nitroaldol condensation reaction.
Keywords: cooperative catalysts; Knoevenagel condensation; mesoporous materials; Nanostructures; nitro aldol reaction

Studies of synergy between metal-support interfaces and selective hydrogenation of HMF to DMF in water - Goyal, Reena; Sarkar, Bipul; Bag, Arijit; Siddiqui, Nazia; Dumbre, Deepa K.; Lucas, Nishita; Bhargava, Suresh Kumar; Bordoloi, Ankur (Journal of Catalysis, 2016)
Metal-support interfaces play a very important role in heterogeneous catalysis. The interfacial interactions not only are responsible for stabilizing the necessary oxidation state to facilitate the reaction but also enhance the stability of the catalyst system. Nano dispersion of Ni on mesoporous nitrogen-rich carbon material has been achieved using two different synthesis methods. It was observed that nickel (0) gets stabilized by strong interfacial interaction with the nitrogen atoms of the support material, and the material was found to be very economic and efficient for the conversion of HMF to DMF in aqueous medium. The material shows >= 99% conversion to 5-(hydroxymethyl) furfural (HMF) within 6 h of reaction with 98.7% DMF selectivity. A unique correlation between synthesis methods and particle sizes with catalytic performance has been observed for these newly developed materials. Furthermore, a DFT calculation has been performed to predict the reaction mechanism. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: biofuels; Biomass; Hydrogenation; mesoporous carbon; Ni-CNx

Process development for crystalline xylitol production from corncob biomass by Pichia caribbica - Dasgupta, Diptarka; Sidana, Arushdeep; Sarkar, Bipul; More, Snehal; Ghosh, Debashish; Bhaskar, Thallada; Ray, Anjan (Food and Bioproducts Processing, 2022)
Xylitol, a commodity chemical, is widely used in nutraceutical and pharmaceutical formulations. Microbial xylitol production is a promising alternative to mitigate current industrial practice issues and offers an environment-friendly sustainable conversion route. This study demonstrates a bioprocess for xylitol production from corncob using a mesophilic yeast Pichia caribbica. Corncob was hydrolyzed by dilute acid and steam explosion to recover fermentable xylose and used as the feed for xylitol production. Activated carbon treatment (3% w/v) completely removed the biomass-derived inhibitors furfural and hydroxymethyl furfural from the liquid hydrolysate. The fermenting yeast Pichia caribbica produced 124.1 +/- 0.45 g/L xylitol from the detoxified and concentrated corncob hydrolysate with a high yield of 0.80 +/- 0.02 g/g. The crystallized xylitol with 96.5% purity demonstrated no harmful effects on the cell line used as a control for the in-vitro toxicity studies. This proof of concept can be applied to help scale up for bio-refinery-based large-scale production of xylitol from corncob biomass.(c) 2022 Institution of Chemical Engineers. Published by Elsevier Ltd. All rights reserved.
Keywords: Biomass; Corncob; Detoxification; Fermentation; Toxicity analysis; xylitol

Process development for detoxification of corncob hydrolysate using activated charcoal for xylitol production - Ahuja, Vishal; Kshirsagar, Siddheshwar; Ghosh, Prasenjit; Sarkar, Bipul; Sutar, Ajit; More, Snehal; Dasgupta, Diptarka (Journal of Environmental Chemical Engineering, 2022)
The work describes process development for detoxification of corncob hydrolysate using activated carbon for microbial xylitol production. Activated carbon was used as an adsorbent to completely remove the major fermentation inhibitors obtained during dilute acid and steam explosion of biomass. A xylitol yield of 0.78 g/g was achieved from the detoxified hydrolysate in a 5 L fermenter by Pichia caribbica. The spent carbon was effectively regenerated and used for three consecutive cycles of operation. The successive regeneration and reuse of carbon could reduce the operational cost by similar to 38% and be used as a reference dataset for process scale-up and cost-effective xylitol production.
Keywords: Activated charcoal; Detoxification; Fermentation; Regeneration; xylitol

Enzymatic biodegradation of used engine oil using a novel lipase derived from renewable feedstocks - Tracy, Preetanshika; Dasgupta, Diptarka; Ashok, Patel Pratima; More, Snehal; Sarkar, Bipul; Porwal, Jyoti; Tripathi, Deependra (World Journal of Microbiology & Biotechnology, 2025)
This study introduces an eco-friendly enzymatic approach for biodegrading used engine oil, utilizing a novel lipase from the mesophilic yeast strain Pichia Caribbica. The yeast was cultured in detoxified corncob hydrolysate with used cooking oil as an inducer. OVAT study confirmed that the optimal pH and temperature for lipase production by the strain was 7.0 and 25 degrees Celsius, respectively, with lipase activity of 70 IU/mL. The enzyme effectively degraded similar to 46% of used engine oil over a period of 15 days. Gas Chromatography-Mass Spectrometry (GC-MS) and FT-IR analysis confirmed a significant reduction in hydrocarbon concentrations and the emergence of new functional groups, confirming the enzyme's ability to degrade complex hydrocarbons into less toxic derivatives. These findings highlight the lipase's potential as an effective biocatalyst for eco-friendly bioremediation of oil-contaminated environments, such as soils and aquatic systems, while also emphasizing its role in environmental management through the reuse of waste by-products in enzyme production, thus reducing the environmental impact of improper waste disposal.
Keywords: Biodegradation; Lipase; PC5703; Used cooking oil; Used engine oil